Curating experience: Composition as cultural technology – a conversation. Issue 2 (15th March 2021) - Molitor, Claudia; Magnusson, Thor
Abstract : This conversation between Thor Magnusson and Claudia Molitor introduces the idea of composition as cultural technology, where compositions are understood as systems that create spaces within which 'things' can occur and can be explored. In this conception of composition, the composer becomes the curator of an experience for an audience, shifting the focus of the work on the encounter of the audience. Talking about some of Molitor's pieces from the past decade, the discussion explores how these ideas can manifest in compositional practice.